Countermovement-jump and pull-up performance before and after a swimming race in preparatory and competitive phases of a swimming season - Gonzalez-Rave, J. M.; Sorgente, V.; Agudo-Ortega, A.; Rodrigo-Carranza, V.; Psycharakis, S.; Turner, A. P. (International Journal of Sports Physiology and Performance, 2024)
Purpose Monitoring performance athletes` training responses can be efficiently completed at competitive events. This study aimed to explore the changes in swimming, countermovement-jump (CMJ), and pull-up (PU) performance following training across a competitive phase, as well as immediately before and after each race.